Fluid flow due to combined convection in lid-driven enclosure having a circular body - Öztop, Hakan Fehmi; Zhao, Zepu; Yu, Bo (Elsevier Science Inc, 2009)
The present work is aimed to study mixed convection heat transfer characteristics for a lid-driven air flow within a square enclosure having a circular body. Flows are driven by the left lid, which slides in its own plane constant velocity. This wall is isothermal and it moves up or down in y direction while the other walls remain stationary. The horizontal walls are adiabatic. The cavity is differentially heated and the left wall is maintained at a higher temperature than the right wall. Three different temperature boundary conditions were applied for the inner cylinder as adiabatic, isothermal or conductive. The computation is carried out for wide ranges of Richardson numbers, diameter of inner cylinder and center and location of the inner cylinder. It was found that the most effective parameter on flow field and temperature distribution is the orientation of the moving lid. The circular body can be a control parameter for heat and fluid flow. An interesting obtained result that the thermal conductivity becomes insignificant for small values of diameter of the circular body. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Mixed convection; Enclosures; Lid-driven cavity; Inserted body